The Use of Plain Language in Legislation: A Case Study of Civil and Commercial Code1 - อารีมิตร, วิชุฎา (Huachiew Chalermprakiet Law Journal, 2021)
The objectives of the article were to study was to investigate the guidelines for using plain language in legislation for solving the problem of complicated language used in Thai laws. The scope of the study focused on specifically exploring the Civil and Commercial Code, which was related to the rights and duties of common people. The study methods included research from books, articles, research papers, thesis work and other related documents. As a result, Thai legal language in civil and commercial code was found to have problems in the language that is difficult to read and understand due to the influence of the legal language and the change in society from the past. At a result, the current legal language is one of the obstacles for law users and law enforcers. Therefore, there should be further development in legal legislation by using plain language to enact civil and commercial codes.